Diversity of Cryptosporidium in common voles and description of Cryptosporidium alticolis sp. n. and Cryptosporidium microti sp. n. (Apicomplexa: Cryptosporidiidae) - Horčičková, Michaela; Čondlová, Šárka; Holubová, Nikola; Sak, Bohumil; Květoňová, Dana; Hlásková, Lenka; Konečný, Roman; Sedláček, František; Clark, Mark; Giddings, Catherine; McEvoy, John; Kváč, Martin (Parasitology, 2019)
Fecal samples from wild-caught common voles (n = 328) from 16 locations in the Czech Republic were screened for Cryptosporidium by microscopy and PCR/sequencing at loci coding small-subunit rRNA, Cryptosporidium oocyst wall protein, actin and 70 kDa heat shock protein. Cryptosporidium infections were detected in 74 voles (22.6%). Rates of infection did not differ between males and females nor between juveniles and adults. Phylogenetic analysis revealed the presence of eight Cryptosporidium species/genotypes including two new species, C. alticolis and C. microti. These species from wild-caught common voles were able to infect common and meadow voles under experimental conditions, with a prepatent period of 3-5 days post-infection (DPI), but they were not infectious for various other rodents or chickens. Meadow voles lost infection earlier than common voles (11-14 vs 13-16 DPI) and had significantly lower infection intensity. Cryptosporidium alticolis infects the anterior small intestine and has larger oocysts (5.4 × 4.9 µm), whereas C. microti infects the large intestine and has smaller oocysts (4.3 × 4.1 µm). None of the rodents developed clinical signs of infection. Genetic and biological data support the establishment of C. alticolis and C. microti as separate species of the genus Cryptosporidium.
Keywords: kur domácí; protozoální DNA; Feces; sekvence nukleotidů; polymerázová řetězová reakce; Male; Microscopy, Interference; genetická variace; Experimental infection; kryptosporidióza; fylogeneze; Chickens; fluorescenční mikroskopie; Rodentia; Česká republika; Cryptosporidiosis; Phylogeny; interferenční mikroskopie; myši inbrední BALB C; prevalence; Murinae; Gastrointestinal Tract; voles; mužské pohlaví; sekvenční seřazení; nemoci hlodavců; DNA, Protozoan; RNA, Ribosomal; Mice, Inbred BALB C; Czech Republic; krysa rodu Rattus; Animals; Microscopy, Fluorescence; ženské pohlaví; Microscopy, Electron, Scanning; RNA ribozomální; zvířata; Rats; myši inbrední C57BL; Arvicolinae; Prevalence; gastrointestinální trakt; myši; molecular analyses; Rodent Diseases; Cryptosporidium; Mice, Inbred C57BL; Polymerase Chain Reaction; Base Sequence; phylogeny; Genetic Variation; Mice; Female; mikroskopie elektronová rastrovací; feces; oocyst size; Sequence Alignment